Prediksi Kefatalan dari Mutasi Missense dan Frameshift pada Varian Gen ULK2 Berpotensi Mengganggu Fungsi Autophagy pada Manusia - Pradan, Erlan; Herliana, Fadhilla Ika; Putri, Vanisa Pricilia; Siregar, Tegar Adriansyah Putra (FORIKES, 2025)
The Unc-51 like kinase 2 (ULK2) protein plays a role in the formation of autophagosomes, a type of cellular compartment. ULK2 acts as an initiator in regulating the autophagy process, interacting with various other proteins in its regulation. ULK2 can experience disruptions in the process, one of which is caused by mutations. Genetic variations such as missense and frameshift mutations can cause changes in the three-dimensional structure of the protein, thereby disrupting cell performance and function. Therefore, the purpose of this study was to determine the distribution of genetic variations or mutations in the ULK2 gene in humans, as well as to determine the fatality rate of missense and frameshift mutations in ULK2 gene variants using PolyPhen-2 software. This type of study is a descriptive observational study with a bioinformatics analysis approach to predict the fatality rate of missense and frameshift mutations in ULK2 gene variants. The data source is genetic variant data of the ULK2 gene accessed and collected from the NCBI dbSNP (Database of Single Nucleotide Polymorphism) database. The research variables were analyzed using PolyPhen-2 software. The analysis results showed that 36% of ULK2 gene variants with missense and frameshift mutations were considered benign, 15% were possibly damaging, and 49% were probably damaging. Meanwhile, 27.27% of frameshift mutations in the ULK2 gene were considered benign, 13.63% were possibly damaging, and 59.09% were probably damaging. In conclusion, predicting the lethality of missense and frameshift mutations in ULK2 gene variants using PolyPhen-2 software has the potential to disrupt protein functionality and autophagy processes based on their lethality level.Keywords: Unc-51 like kinase 2; single nucleotide polymorphism; missense; frameshift; PolyPhen-2 ABSTRAK Protein Unc-51 like kinase 2 (ULK2) berperan dalam pembentukan autophagosome, salah satu jenis kompartemen seluler. ULK2 memiliki peran sebagai inisiator dalam mengatur proses autophagy, berinteraksi dengan berbagai protein lainnya dalam regulasi tersebut. ULK2 dapat mengalami gangguan dalam prosesnya, salah satunya disebabkan terjadinya mutasi. Variasi genetik seperti mutasi missense dan frameshift dapat menyebabkan perubahan struktur tiga dimensi dari protein sehingga akan mengganggu kinerja dan fungsi sel. Oleh karena itu, tujuan penelitian ini adalah untuk mengetahui distribusi variasi genetik atau mutasi yang dimiliki oleh gen ULK2 pada manusia, serta untuk mengetahui tingkat kefatalan dari mutasi missense dan frameshift pada varian gen ULK2 dengan menggunakan piranti lunak PolyPhen-2. Jenis penelitian ini adalah deskriptif observasional dengan pendekatan analisis bioinformatika untuk mengetahui prediksi tingkat kefatalan mutasi missense dan frameshit dari varian gen ULK2. Sumber data merupakan data varian genetik gen ULK2 yang diakses dan dikumpulkan dari database NCBI dbSNP (Database of Single Nucleotida Polymorphism). Variabel penelitian dianalisis dengan piranti lunak PolyPhen-2. Hasil analisis menunjukkan bahwa gen ULK2 yang mengalami mutasi missense dan frameshift, varian gen ULK2 yang mengalami mutasi missense menunjukkan bahwa 36% dianggap benign, 15% possibly damaging, dan 49% probably damaging. Adapun mutasi frameshift pada gen ULK2 memberikan hasil bahwa 27,27% dianggap benign, 13,63% possibly damaging, dan 59,09% probably damaging. Sebagai kesimpulan, prediksi kefatalan mutasi missense dan frameshift terhadap varian gen ULK2 menggunakan piranti lunak PolyPhen-2 berpotensi mengganggu fungsionalitas dari protein dan proses autophagy berdasarkan tingkat kefatalannya.Kata kunci: Unc-51 like kinase 2; single nucleotida polymorphism; missense; frameshift; PolyPhen-2